Epstein–Barr virus positivity among surgically resected intramucosal gastric cancer. Issue 5 (6th June 2018) - Murai, Katsuyuki; Kakushima, Naomi; Sugino, Takashi; Yoshida, Masao; Kawata, Noboru; Tanaka, Masaki; Takizawa, Kohei; Muramatu, Koji; Kusafuka, Kimihide; Bando, Etsuro; Ono, Hiroyuki
Abstract : Epstein–Barr virus‐associated gastric cancer (EBV‐GC) accounts for approximately 8% of gastric cancers. However, little is known regarding intramucosal EBV‐GC. The present study aimed to evaluate endoscopic and clinicopathological characteristics of intramucosal EBV‐GC. Pathological data of 172 patients with 173 intramucosal gastric cancers who received gastrectomy with lymph node dissection were obtained for review. EBV‐encoded small RNA in situ hybridization (EBER‐ISH) was carried out using a tissue microarray block. Eight intramucosal early gastric cancers (4.6%) were EBER‐ISH positive in which no cases had any lymph node metastasis. Macroscopic types were either depressed or flat, dominant histology was mixed type of moderate and poorly differentiated adenocarcinoma. In detail, histological features of "lace pattern" or "lymphocyte infiltration into the stroma or cancer nests" were observed.